The impact of social media marketing on brand loyalty - ERDOĞMUŞ, ZEYNEP İREM (ELSEVIER SCIENCE BV, 2012)
Building and maintaining brand loyalty are one of the central themes of research for marketers for a very long time. Marketers have utilized various means to maintain the brand loyalty of their customers. One of the recent means is the social media marketing. The aim of this study is to identify the effect of social media marketing on brand loyalty of the consumers, given that the concept is receiving increasing attention from marketing academia and practitioners. The scope of the study consists of customers who follow at least one brand on the social media in Turkey and the data were collected through the administration of a structured questionnaire with a sample of 338 people and tested via stepwise multiple regression analysis. The results of the study showed that brand loyalty of the customers is positively affected when the brand (1) offers advantageous campaigns, (2) offers relevant content, (3) offers popular contents, (4) appears on various platforms and offers applications on social media; were used by using SPSS 17.0 version. Customers prefer to share music, technological-related, and funny contents on social media platforms. Based on our results, this study can be considered as a pioneer in this new area of marketing, and propose several tactics for the practitioners.
Keywords: social media marketing; brand loyalty; content; promotion